Bank profitability and macroeconomy: evidence from Lithuania - Naruševičius, Laurynas (Technological and Economic Development of Economy, 2018)
The purpose of this paper is to investigate the relationship between profitability of the Lithuanian banking sector and its internal and external determinants. We use the panel error correction model to assess long-term and short-term determinants of items from bank income statements (net interest income, net fee and commission income and operating expenses). The results of the pooled mean group estimator show that bank size and real GDP are the main determinants in the long-term. Meanwhile, empirical examination suggests various variables as short-term determinants of income statement items. The pooled mean group estimation technique and the analysis of separate income statement items enable us to have a better insight into the Lithuanian banking sector and determinants of its revenue and expenses.First published online: 16 Mar 2017